Modification and experimental validation of the Forrestal-Warren perforation model for high hardness armor steel plates of intermediate thickness - Radovan Djurovic; Predrag Elek; Milos Markovic; Dejan Jevtic (Defence Technology)
This paper proposes a modification of the Forrestal-Warren perforation model aimed at extending its applicability range to intermediately-thick high-hardness armor steel plates. When impacted by armor-piercing projectiles, these plates tend to fail through adiabatic shear plugging which significantly reduces their ballistic resistance. To address this effect, an approach for determining effective thickness was defined and incorporated into the predictive model. Ballistic impact tests were performed to assess the modification's validity, in which ARMOX 500T steel plates were subjected to perpendicular impacts from 7.62 × 39 mm steel-cored rounds under various velocities. Frequent target failure by soft plugging was observed, as well as the brittle shatter of the hard steel core. Key properties of the recovered plugs including their mass, length and diameter were measured and reported along with the projectiles' residual velocities. Additionally, independent data from the open literature were included in the analysis for further validation. The original Forrestal-Warren model and the novel effective thickness modification were then used to establish the relationship between impact and residual velocities, as well as to determine the ballistic limit velocity. The comparison revealed that the proposed approach significantly improves the model's accuracy, showing a strong correlation with experimental data and reducing deviations to within a few percent. This enhancement highlights the potential of the effective thickness term, which could also be applied to other predictive models to extend their applicability range. Further exploration into other armor steels and impact conditions is recommended to assess the method's versatility.